PTCSC3‐mediated glycolysis suppresses thyroid cancer progression via interfering with PGK1 degradation. Issue 17 (1st August 2021) - Jiang, Bo; Chen, Yong; Xia, Fada; Li, Xinying
Abstract: The Warburg effect (aerobic glycolysis), a hallmark of cancer, serves as a promising target for diagnosis and therapy. Growing evidence indicates that long non‐coding RNAs (lncRNAs) play an important role in aerobic glycolysis of various tumours. However, the correlation between lncRNAs and glycolysis in thyroid cancer cells is still poorly understood. In this study, we showed that lncRNA papillary thyroid cancer susceptibility candidate 3 (PTCSC3) was significantly downregulated in papillary thyroid carcinoma (PTC). Overexpression of PTCSC3 significantly inhibited the aerobic glycolysis and tumour growth of PTC cells. Consistently, PTCSC3 overexpression suppressed tumour progress in vivo. Mechanistically, PTCSC3 inhibits aerobic glycolysis and proliferation of PTC by directly interacting with PGK1, a key enzyme in glycolytic pathway. As a result, PTCSC3 performs its role in PTC development via PGK1 and may be a potential therapeutic target for PTC treatment.